The complex interaction between channel–levee systems and mass transport complexes in the Pliocene–Quaternary Rakhine Basin, offshore Myanmar - Shao, Dali; Fan, Guozhang; Ma, Hongxia; Wang, Haiqiang; Ding, Liangbo; Zuo, Guoping; Lu, Yintao; Xu, Xiaoyong (Frontiers in Earth Science, 2024)
Channel-levee systems and mass-transport complexes (MTCs) are prevalent in deep-water basins, yet their interplay remains enigmatic. This study uses high-resolution 3D seismic data to investigate the architecture of channel-levee systems and MTCs, aiming to explore how channel-levee systems influence the distribution of MTCs in the Rakhine Basin, Bay of Bengal. Two models have been built to illustrate the interaction between channel-levee systems and MTCs. In the first model, large-scale aggradational channel-levee systems created unfilled relief in their overbank environments, which acted as spacially confined topography for subsequent mass-wasting deposits. In this model, the interaction between large-scale channel levee systems and confined MTCs controls the distribution of confined MTCs. In the second model, laterally migrating channel-levee systems do not create such prominent topographic relief in their overbank environments. This characteristic renders them inconsequential in influencing the distribution of subsequent mass-wasting processes. Consequently, spacially extensive MTCs develop within unconfined settings. This configuration give rise to lithological traps, which might be common, and represent potential drilling targets on continental margins. This study could contribute to a better understanding of the interplay between channel-levee systems and MTCs and have some enlightenment on looking to provide some insight into the search for lithological traps in the Rakhine Basin.